2018
DOI: 10.7717/peerj.4976
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome profiling by RNA-Seq reveals differentially expressed genes related to fruit development and ripening characteristics in strawberries (Fragaria×ananassa)

Abstract: Strawberry (Fragaria × ananassa) is an ideal plant for fruit development and ripening research due to the rapid substantial changes in fruit color, aroma, taste, and softening. To gain deeper insights into the genes that play a central regulatory role in strawberry fruit development and ripening characteristics, transcriptome profiling was performed for the large green fruit, white fruit, turning fruit, and red fruit stages of strawberry. A total of 6,608 differentially expressed genes (DEGs) with 2,643 up-reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 67 publications
2
40
4
Order By: Relevance
“…The expression profiles of the transcription factors (TFs) revealed that the anthocyanin production promoter MYB10 and repressor MYB1 were both significantly lower at the R stage in white PC than in red BS (Figure 3). The transcript levels of the anthocyanin production repressor MYB1 in this study differ from those for FaMYB1 in red F. x ananassa [47], and in red F. vesca [28], seeming to increase at R rather than declining, indicating that it was not functioning as a repressor. In a white F. chiloensis, FcMYB1 was also high at T and R, suppressing anthocyanin accumulation [19].…”
Section: Transcriptional Profiles Of Key Transcription Factors Of Thecontrasting
confidence: 82%
See 1 more Smart Citation
“…The expression profiles of the transcription factors (TFs) revealed that the anthocyanin production promoter MYB10 and repressor MYB1 were both significantly lower at the R stage in white PC than in red BS (Figure 3). The transcript levels of the anthocyanin production repressor MYB1 in this study differ from those for FaMYB1 in red F. x ananassa [47], and in red F. vesca [28], seeming to increase at R rather than declining, indicating that it was not functioning as a repressor. In a white F. chiloensis, FcMYB1 was also high at T and R, suppressing anthocyanin accumulation [19].…”
Section: Transcriptional Profiles Of Key Transcription Factors Of Thecontrasting
confidence: 82%
“…Medina-Puche et al [29] suggested that MYB10 may regulate most or all of the flavonoid pathway genes in the early and late stages of fruit development in F. x ananassa. There was no apparent expression of MYB10 at G1 and more expression in red than white at G2 in our study, as with FaMYB10 in F. x ananassa [29,47], but MYB10 was lower in white PC at stage R in comparison to BS. Overexpression of FvMYB10 in F. vesca greatly increased anthocyanin concentration [26], but other flavonoid levels were not affected except for p-coumaroyl glucose, suggesting MYB10 may only act on the final anthocyanin-related branch.…”
Section: Transcriptional Profiles Of Key Transcription Factors Of Thecontrasting
confidence: 49%
“…Our results are supported by previous studies reporting that bZip were induced by various environmental cues. Indeed it was revealed that they play a pivotal role in responses to cold stress in peach and enhance water use efficiency in almond-peach rootstocks (Hu et al, 2018). WRKYs putative motifs were restricted to M6 and were exclusively activated in leaf tissue under hyper-hydricity (HH) stress.…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptome sequencing (RNA-Seq) has strongly accelerated research on host-pathogen interactions in plants such as rice [31], maize [32], cucumber [33], watermelon [34] and strawberry [35]. Avr4/Cf-4and Avr9/Cf-9-dependent defense gene expression has been confirmed by cDNA-AFLP (cDNA-amplified fragment length polymorphism) analysis [36].…”
Section: Introductionmentioning
confidence: 99%